Analysis of Dance Movement Structure Kabela At the Mokosambe Studio, Mopait Village - Mery Aprillia Damopilii; Riana Diah Sitharesmi; Nurlia Djafar; meryaprilliadamopolii@gmail.com; Trubus Semiaji (International Journal of Science and Environment (IJSE), 2026)
This study aims to describe the movement structure of the kabela dance at the Mokosambe Studio, Mopait Village, Bolaang Mongondow Regency. This study uses a qualitative approach with a descriptive research type. Data collection techniques are carried out through observation, interviews, and documentation. Data sources in this study were obtained from studio managers, cultural figures, dancers, and various documentation related to the kabela dance. The data analysis technique uses grounded theory by analyzing data systematically through identifying and grouping dance movement structures based on the results of field research. The results show that the kabela dance is a traditional dance that functions as a welcoming dance for guests and has cultural values ​​​​of the Bolaang Mongondow community. The movement structure of the kabela dance consists of several types of movements, namely entering the arena, saluting, arranging flowers, glancing to the right and left, surrounding the kabela, kayang, making up, scattering flowers, and closing movements. Each movement has a regular structure and is performed continuously to the accompaniment of traditional music. Kabela dance movements are dominated by soft, regular, and polite movements that reflect an attitude of respect for guests. In addition, the kabela dance is also supported by supporting elements such as female dancers, traditional salu' clothing, kabela props, and traditional musical accompaniment in the form of drums, gongs, and flutes. Based on the results of this study, it can be concluded that the kabela dance has a systematic movement structure and contains aesthetic and cultural values ​​​​of the Bolaang Mongondow community. Therefore, the kabela dance needs to be continuously preserved as one of the regional cultural heritage.